DRAMATURGY AND THEATRE AS STRUCTURE INTERVENTIONS IN DRIVING ORGANISATIONAL CHANGE - A QUALITATIVE STUDY - D’Souza, Anil Reynold (Digital Repository of Theses, 2023)
The application of drama in a sociological context was influenced by Erving Goffman and Kenneth Burke through their development of understanding human engagement through social action. When change is not systemically driven at the level of individual values & beliefs, there continues to be tension due to the gap caused by current behaviour in the workplace and what is ‘desired / preferred behaviour’. This tension, which is largely mitigated through external symbols and reward, creates a lack of authentic relationships and behaviours that people are compelled to demonstrate. Since these behaviours may not authentic, the effectiveness criteria requires external levers and authority to drive performance. Performance is thus, not a joyful process of authentic self-expression, thereby causing anxiety, stress and greater potential for conflict, confrontations, lower job satisfaction and attrition. The study emanates from the submission that change management interventions need to employ a greater focus on developing value congruence through a significant emotionally compelling device rather than a pure cognitive learning devices. The Theatre Arts are an art based dialogic intervention and can applied as a distinctive change inducing intervention that emphasizes on changing the nature of conversations that usually take place in an organization.